A multiparametric heart failure score at baseline is associated with long-term outcome in patients with remotely monitored implantable cardioverter-defibrillators: A pooled analysis of 9 clinical trials - D'Onofrio, Antonio; Solimene, Francesco; Bulava, Alan; Shoda, Morio; Klein, Cedric; Gargaro, Alessio; Timmel, Tobias; Giacopelli, Daniele; Botto, Gianluca (Heart rhythm, 2025)
BACKGROUND: To predict worsening heart failure hospitalizations (WHFHs), the HeartInsight multiparametric algorithm calculates a heart failure (HF) Score based on temporal trends of physiologic parameters obtained through automatic daily remote monitoring of implantable cardioverter-defibrillators (ICDs). OBJECTIVE: We studied the association of the baseline HF Score, determined at algorithm activation, with long-term patient outcomes. METHODS: Data from 9 clinical trials were pooled, including 1841 ICD patients with a preimplantation ejection fraction ≤35%, New York Heart Association class II/III, and no long-standing atrial fibrillation. The primary end point was a composite of death or WHFH. RESULTS: After a median follow-up of 631 days (interquartile range, 385-865 days), there were 243 WHFHs in 173 patients (9.4%) and 122 deaths (6.6%), 52 of which (42.6%) were cardiovascular. The primary end point occurred in 265 patients (14.4%). A multivariable time-to-first-event analysis showed that a high baseline HF Score (>23, as determined by a time-dependent receiver operating characteristics curve analysis) was significantly associated with the occurrence of the primary end point (adjusted hazard ratio [HR], 2.05; 95% confidence interval [CI], 1.54-2.71; P < .0001), all-cause death (HR, 2.37; CI, 1.56-3.58; P < .0001), cardiovascular death (HR, 2.19; CI, 1.14-4.22; P = .019), and WHFH (HR, 1.91; CI, 1.35-2.71; P = .0003). In a hierarchical event analysis of all-cause death as the outcome with highest priority and WHFHs as repeated event outcomes, the win ratio was 2.47 (CI, 1.89-3.24; P < .0001). CONCLUSION: Based on a retrospective analysis of clinical trial data with adjudicated events, baseline HF Score derived from device-monitored variables was able to stratify patients at higher long-term risk of death or WHFH.
Keywords: Stroke Volume; klinické zkoušky jako téma; Risk stratification in heart failure patients; Clinical Trials as Topic; Female; Worsening heart failure hospitalization; ženské pohlaví; Heart Failure; Time Factors; časové faktory; Implantable defibrillator; lidé; srdeční selhání; následné studie; Algorithms; hospitalizace; Follow-Up Studies; Male; Remote monitoring; Aged; Hospitalization; tepový objem; algoritmy; Defibrillators, Implantable; lidé středního věku; senioři; mužské pohlaví; Death; defibrilátory implantabilní; Middle Aged; Heart failure score; Humans